Cloning, characterization, and functional analysis of acetyl-CoA C-acetyltransferase and 3-hydroxy-3-methylglutaryl-CoA synthase genes in Santalum album - Meiyun Niu (Nature Portfolio, 2021)
Abstract Sandalwood (Santalum album L.) is famous for its unique fragrance derived from the essential oil of heartwood, whose major components are santalols. To understand the mechanism underlying the biosynthesis of santalols, in this study, we cloned two related genes involved in the mevalonate pathway in S. album coding for acetyl-CoA C-acetyl transferase (AACT) and 3-hydroxy-3-methyglutary-CoA synthase (HMGS). These genes were characterized and functionally analyzed, and their expression profiles were also assessed. An AACT gene designated as SaAACT (GenBank accession No. MH018694) and a HMGS gene designated as SaHMGS (GenBank accession No. MH018695) were successfully cloned from S. album. The deduced SaAACT and SaHMGS proteins contain 415 and 470 amino acids, and the corresponding size of their open-reading frames is 1538 bp and 1807 bp, respectively. Phylogenetic trees showed that the SaAACT protein had the closest relationship with AACT from Hevea brasiliensis and the SaHMGS proteins had the highest homology with HMGS from Siraitia grosvenorii. Functional complementation of SaAACT and SaHMGS in a mutant yeast strain deficient in these proteins confirmed that SaAACT and SaHMGS cDNA encodes functional SaAACT and SaHMGS that mediate mevalonate biosynthesis in yeast. Tissue-specific expression analysis revealed that both genes were constitutively expressed in all examined tissues (roots, sapwood, heartwood, young leaves, mature leaves and shoots) of S. album, both genes showing highest expression in roots. After S. album seedlings were treated with 100 μM methyl jasmonate, the expression levels of SaAACT and SaHMGS genes increased, suggesting that these genes were responsive to this elicitor. These studies provide insight that would allow further analysis of the role of genes related to the sandalwood mevalonate pathway in the regulation of biosynthesis of sandalwood terpenoids and a deeper understanding of the molecular mechanism of santalol biosynthesis.